CSR Moderation on The Impact of Financial Performance on The Firm Value of Coal Mining Companies Listed on The IDX - Naufaldy Pasaribu, Ahmad; Siregar, Hermanto; Hasanah, Nur (Pelopor Publikasi Akademika, 2025)
This study aims to analyze the effect of financial performance on firm value with Corporate Social Responsibility (CSR) as a moderating variable. Financial performance is measured using financial indicators such as Return on Equity (ROE) and Net Profit Margin (NPM), while firm value is represented by Price to Book Value (PBV). The type of research used is quantitative research. The variables used in this study consist of independent variables, namely Financial Performance, dependent variables, namely company value and moderating variables, namely Corporate Social Responsibility (CSR). The population used in this research is 34 coal mining companies. The sampling technique used purposive sampling with a sample obtained of 19 companies. Data collection techniques using documentation by taking data on the Indonesia Stock Exchange (IDX). Data analysis techniques used using Descriptive Statistical Analysis, regression analysis and Moderate Regression Analysis. The results showed that financial performance as measured by ROE has a positive and significant influence on company value. Meanwhile, NPM has no influence on company value. In addition, CSR is proven to moderate the ROE relationship positively, where companies with good CSR implementation show a higher increase in firm value than companies with low levels of CSR. However, CSR has not been able to moderate NPM on company value. The conclusion of this study is that Return On Equity affects the company's value. Net Profit Margin has no effect on company value, while CSR only moderates the effect of ROE on company value.